A Nomogram of Combining IVIM‐DWI and MRI Radiomics From the Primary Lesion of Rectal Adenocarcinoma to Assess Nonenlarged Lymph Node Metastasis Preoperatively. Issue 3 (28th January 2022) - Jia, Haodong; Jiang, Xueyan; Zhang, Kaiyue; Shang, Jin; Zhang, Yu; Fang, Xin; Gao, Fei; Li, Naiyu; Dong, Jiangning
Abstract : Background: Lymph node (LN) staging plays an important role in treatment decision‐making. Current problem is that preoperative detection of LN involvement is always highly challenging for radiologists. Purpose: To explore the value of the nomogram model combining intravoxel incoherent motion diffusion‐weighted imaging (IVIM‐DWI) and radiomics features from the primary lesion of rectal adenocarcinoma in assessing the non‐enlarged lymph node metastasis (N‐LNM) preoperatively. Study Type: Retrospective. Population: A total of 126 patients (43% female) comprising a training group ( n  = 87) and a validation group ( n  = 39) with pathologically confirmed rectal adenocarcinoma. Field Strength/Sequence: A 3.0 Tesla (T); T2 −weighted imaging (T2 WI) with fast spin‐echo (FSE) sequence; IVIM‐DWI spin‐echo echo‐planar imaging sequence. Assessment: Based on pathological analysis of the surgical specimen, patients were classified into negative LN (LN−) and positive LN (LN+) groups. Apparent diffusion coefficient (ADC), diffusion coefficient (D), pseudo diffusion coefficient (D*) and microvascular volume fraction (f) values of primary lesion of rectal adenocarcinoma were measured. Three‐dimensional (3D) radiomics features were measured on T2 WI and IVIM‐DWI. A nomogram model including IVIM‐DWI and radiomics features was developed. Statistical Tests: General_univariate_analysis and multivariate logistic regression were used for radiomics features selection. The performance of the nomogram was assessed by the receiver operating characteristic (ROC) curve, calibration, and decision curve analysis (DCA). Results: The LN+ group had a significantly lower D* value ([13.20 ± 13.66 vs. 23.25 ± 18.71] × 10 −3  mm 2 /sec) and a higher f value (0.43 ± 0.12 vs. 0.34 ± 0.10) than the LN− group in the training cohort. The nomogram model combined D*, f, and radiomics features had a better evaluated performance (AUC = 0.864) than any other model in the training cohort. Date Conclusion: The nomogram model including IVIM‐DWI and MRI radiomics features in the primary lesion of rectal adenocarcinoma was associated with the N‐LNM. Evidence Level: 4 Technical Efficacy: Stage 2